Analysis Condition of Coral Reef Covering in Pramuka Island Waters, Seribu Islands using Line Intercept Transect (LIT) Method - Rega Permana; Nora Akbarsyah; Pringgo KDNY Putra; Aulia Andhikawati (Universitas Negeri Surabaya, 2020)
The coral reef ecosystem is one of the typical tropical ecosystems with high biodiversity which has an important role both biologically, ecologically, physically as well as socially and economically. Several coral reef areas in Indonesia were reported to have suffered damage, not only due to climate change which has an impact on rising sea surface temperatures and ocean acidification but also due to anthropogenic factors and irresponsible management of marine tourism. This study aimed to analyze the condition of coral reefs based on covering in Pramuka Island, which is one of the famous tourist destinations in the Seribu Islands. The study was conducted using Line Intercept Transect (LIT) method at predetermined coordinate points. The results showed that the dominant coral reef life form was Acropora Submassive (ACS), namely 18.9%, and Acropora Branching (ACB) as much as 12.48%. Besides, the types of life forms found were coral foliase (9.42%), Miliepora Coral (9.2%), Coral Massive (4.8%), Acropora Encrustring (4.24%), and so on. Based on the results of this study, it can be concluded that the condition of coral reefs in Pramuka Island is still relatively good with a total coral cover percentage of 72.38%. Efforts to protect the coral reef ecosystem in this area need to be considered so that its condition can be maintained.